Medieval Domestic Devotion - Deane, Jennifer Kolpacoff (History compass, 2013)
For generations, scholars of history, religion, anthropology, theology and other disciplines have pored over texts, artifacts, and ritual behaviors, seeking to understand better the nature of medieval religious experience. Yet until recently, the intriguing intersections of home and the holy during the Middle Ages received little sustained attention - a circumstance due to issues of both limited sources and historiographical emphasis. Informed by interdisciplinary contributions from gender studies, anthropology, spatial studies, and other fields, however, recent research has cast new light on how medieval women and men constructed and enacted devotional practice in domestic spaces. This article introduces readers to both the historical and historiographical patterns shaping current understandings of domestic devotion during the Middle Ages. After a brief survey of key scholarly shifts in the late twentieth century that set the stage for new approaches, focus turns to ways in which medieval people encountered the sacred at home: these include prayer, reading (devotional books and books of hours), and the use of material objects in spiritual practice such as relics, rosaries, and portable altars. The final section suggests several possible directions for future research.